2021
DOI: 10.4103/1995-7645.304296
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 in Mazandaran province, Iran

Abstract: Objective: To determine the seroprevalance of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies in the general population of Mazandaran province in Iran and to estimate the percentage of asymptomatic, mild, and severe infections. Methods: We chose 1 588 inhabitants of Mazandaran province with cluster sampling. We measured their SARS-CoV-2 immunoglobulin M (IgM) and immunoglobulin G (IgG) serum levels. Demographics, risk factors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…In the present study, a geographical variation was observed in estimating the seroprevalence, which ranged from 2.3 to 61.6%. Our seroprevalence estimate was less than that reported from Semnan (19.3%, 95% CI, 14.0-26.7) in late June 2020 [14] and more than Mazandaran's 15.26% (95% CI: 12.97%-17.79%) in May 2020 [15]. Between April 17th and June 2nd, 2020, in a large and population-based seroprevalence study using obtained sera samples from 5372 individuals with a high risk of exposure to SARS-CoV-2 and 3530 individuals from the general population in 18 cities in 17 Iranian provinces, adjusted seroprevalence was estimated 20% (18.5-21.7) and 17.1% (95% CI 14.6-19.5) ranged from 72.6% (95% CI: 53.9-92.8) to 1.7% (95% CI: 0•0-6•0), respectively [16].…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…In the present study, a geographical variation was observed in estimating the seroprevalence, which ranged from 2.3 to 61.6%. Our seroprevalence estimate was less than that reported from Semnan (19.3%, 95% CI, 14.0-26.7) in late June 2020 [14] and more than Mazandaran's 15.26% (95% CI: 12.97%-17.79%) in May 2020 [15]. Between April 17th and June 2nd, 2020, in a large and population-based seroprevalence study using obtained sera samples from 5372 individuals with a high risk of exposure to SARS-CoV-2 and 3530 individuals from the general population in 18 cities in 17 Iranian provinces, adjusted seroprevalence was estimated 20% (18.5-21.7) and 17.1% (95% CI 14.6-19.5) ranged from 72.6% (95% CI: 53.9-92.8) to 1.7% (95% CI: 0•0-6•0), respectively [16].…”
Section: Discussioncontrasting
confidence: 86%
“…Z: for 95% confidence level is 1.96 P: Prevalence of positive COVID-19 based on the results of previous seroepidemiological studies in Kermanshah (15), which was 15%. d: d is the absolute precision, also called the margin of error, which was taken into account in a study of one-quarter of the prevalence, which was 0.0157.…”
Section: Sample Size and Sampling Strategymentioning
confidence: 99%
See 1 more Smart Citation